STUDENTS’ PERCEPTION ON DIGITAL BASED LEARNING IN ICT CLASS OF UNM - Muh. Mushaddiq A; Amirullah Abduh; Amra Ariyani (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This research is descriptive quantitative analysis research that aims to determine students' perceptions of digital-based learning in the ICT class at Universitas Negeri Makassar. The population in this study was 150 students of the English education program who programmed ICT courses which were divided into four classes in the Class of 2019 with a total of 38 students as a sample. Research data were obtained by questionnaire. The technique of analyzing data used in this research is a descriptive analysis using Microsoft Excel. Based on data that has been processed, students' perceptions of digital-based learning are divided into five indicator categories, namely: Digital Material, Discussion, Exercise, Quiz, and General with the overall average value of perception of 100.58 being in the positive category (92 - 149) which support the claim that using e-learning to supplement Face-to-face teaching improves the learning experience in general and that the online learning has the potential to facilitate students with more alternatives, versatility, assets, and opportunities while also allowing educators to teach using different delivery and evaluation methods.